Transformative experience and informed consent to psychedelic-assisted psychotherapy - Jacobs, Edward (Frontiers in Psychology, 2023)
Just as psychedelic-assisted psychotherapy (PAP) represents a clinical innovation that may need to be accommodated with corresponding theoretical and methodological innovations, there is growing awareness that the tools, normative frameworks, and standard practices of our clinical ethics may also need to be adapted, renewed, or replaced to accommodate its unusual features. Drawing on L. A. Paul's work on “Transformative Experience,” I argue that the acute and long-term effects that are repeatedly reported following the administration of psychedelic drugs, including in clinical contexts, are epistemically inaccessible at the point of deciding to take them. By virtue of both the so-called “mystical” experiences that frequently arise during PAP, and the long-term shifts to outlooks, values, and priorities that can follow treatment, the processes of decision-making that are normatively expected of patients run aground. If this framing is correct, then prospective patients cannot meet the requirement of understanding that is one of the principal analytic components of informed consent. The role of understanding in supporting two functions of informed consent—avoiding unauthorized trespass against patients and supporting values-aligned decision-making—is explored, and I argue that, while the normative standard for the first function may be met by extant suggestions for enhancing the consenting process for PAP, the latter function remains unattainable. In light of this, the consequences for the ethical preparation of prospective patients are considered.